Variação ambiental, genotoxicidade e ecotoxicologia de um rio tropical no semiárido brasileiro (PI, Brasil). - Sousa, João Marcelo de Castro e (2015)
Rivers are the most important water resources for human consumption, agricultural, industrial and recreational purposes. In this way, it is essential to have reliable information on water quality for effective management. This need is even more important in semi-arid regions, such as the northeast region of Brazil, which have water shortage problems in densely populated areas, such as the city of Picos and micro-region, where it is located the Guaribas River, the main river of its basin and the 3rd major river of the State of Piauí. This river runs across more than 30 municipalities and in recent years it has been subjected to human and natural disturbances, mainly pollution by domestic and agricultural effluents, together with unfavorable weather conditions throughout the year. The present study aimed to conduct the first environmental and genetic assessment of the Guaribas River, in order to investigate its water quality, and potential toxic and genetic effects along the river course, in the dry and rainy periods between 2013 and 2015. Water samples were analyzed for some physical and chemical variables, such as electrical conductivity (EC), total dissolved solids (TDS), pH, dissolved oxygen (DO), saturated oxygen (SO), temperature (T), nitrate (NO3-), nitrite (NO2-), total phosphorus (TP), biochemical oxygen demand (BOD), sulfate (SO42-), turbidity (turb), chlorine (Cl), color, iron (Fe), zinc (Zn), copper (Cu), chromium (Cr) and aluminum (Al). Besides that, water cytotoxicity and genotoxicity at the cellular level were evaluated with bioassays (Allium cepa test and Micronucleus test) and bioindicators (Allium cepa and Oreochromis niloticus) specific to aquatic toxicology at different sampling sites along the river course. Results of water quality demonstrated that some physical and chemical variables did not comply with the Brazilian Environmental Law (Resolution 357/2005), with values indicating poor water quality, regardless of the period. Principal Component Analysis revealed the main sources of pollution: domestic pollutants (PC1 with 39.50% total variance), organic pollutants (PC2 with 30.31%) and temperature (PC3 with 12.46%) determined the separation between periods. Cluster analysis evidenced the separation of the non-impacted sites (upstream of the city) from the impacted sites (within and downstream of the city). Toxic and genetic results showed cytotoxic and mutagenic effects for surface water samples taken from polluted sites, with the genetic damage positively related to heavy metals (Fe, Zn, Cr, Cu and Al). Also, it was found potentially cyanotoxin-producing cyanobacteria along the river. Therefore, the Guaribas River is a polluted aquatic environment throughout the year in the sites influenced by the major city on its banks (Picos), with release of chemicals causing genetic damage to organisms present in this environment. Thus, it becomes necessary to adopt constant monitoring to improve water quality and eliminate mutagenic agents harmful to human health.